SCHOOL PHYSICAL EDUCATION : PHYSICAL RELATIONSHIP BETWEEN INACTIVITY AND BODY MASS INDEX IN CHILDREN OF VICTORIA HALL OF SAINT ANTONY - PE. (Fiep Bulletin - online, 2014)
A growing number of obese and inactive children . Several factors can be Attributed to this situation , such as technological advances , bad eating habits and lack of physical activity . Therefore , we Performed a sample of 60 children from two schools in the elementary school , 50 % of children in a school that is covered with the physical education classes and 50 % of Those who are not assisted . Some criteria were used in order to determine the level of overweight , obesity and physical activity . The level of physical activity was avaliado using the Physical Activity Questionnaire for Children ( Physical Activity Questionnaire for Older Children , PAQ - C ) . This questionnaire assesses the level of moderate and intense physical activity of children in the seven days prior to application . It Consists of nine questions , each one with values ??ranging from 1 to 5 and the final score is Obtained by averaging the issues , Representing the range of very sedentary ( 1 ) to very active ( 5 ) . Scores 2 , 3 and 4 Indicate the categories sedentary , moderately active and active , respectivamente .. To determine the level of overweight and obesity , we used the standard National Center for Health Statistics ( NCHS ) . The ( BMI = kg / m² ) is expresso in standard deviation units ( Z score) . Cole et al. The Corresponding ( BMI 25kg / m² ) the overweight and 30 kg / m² and obesity in children from two years old .
Keywords: physical inactivity; body mass index and School .